Simultaneous identification of the anaphylactoid components from traditional Chinese medicine injections using rat basophilic leukemia 2H3 and laboratory of allergic disease 2 dual‐mixed/cell membrane chromatography model. Issue 9 (6th February 2018) - Han, Shengli; Lv, Yanni; Kong, Liyun; Sun, Yueming; Fu, Jia; Li, Lingjun; He, Langchong
Abstract: Traditional Chinese medicine (TCM) has been used for prevention and treatment of various diseases for many decades. TCM injection is a new dosage form, with incidence of anaphylactoid reactions increasing every year. In this study, the rat basophilic leukemia 2H3 (RBL‐2H3) and laboratory of allergic disease 2 (LAD2) dual‐mixed/CMC was established and was coupled with an HPLC‐ESI‐IT‐TOF‐MS system to identify the potential allergenic components in Haqing injection. Cinobufagin, piperine, osthole, praeruptorin A, and schizandrin A were screened from Haqing injection via this coupled system. Competitive binding assay showed piperine, praeruptorin A, and schizandrin A acting on MrgprX2 and cinobufagin and osthole act on the IgE receptor. The release of mediators of anaphylaxis results showed cinobufagin and osthole can cause anaphylactoid reactions by triggering the release of β‐hexosaminidase and histamine via IgE‐R. Praeruptorin A and schizandrin A could promote the release of β‐hexosaminidase and histamine via MrgprX2 receptor. In summary, the dual‐mixed/CMC model can significantly improve the efficiency of target component identification from a complex sample. When combined with competitive binding assay and validation of biological activities, this model enables accurate determination of the dual‐target components, offering improved methods for quality control of TCM injections.